Changes in Cultivated Land and Its Effects on Vegetation and Evapotranspiration Characteristics in the Naoli River Basin - YIN Jian; XIA Ruici; WEI Danqi; DING Yi; JIANG Hongtao; LUO Xinyuan (Renmin Zhujiang)
The Naoli River Basin is located in the hinterland of the Sanjiang Plain and is an important grain production area in China.In recent years,with the guarantee of food security and the adjustment of regional agricultural structure in China,there have been significant changes in land use,such as cultivated land expansion and planting structure adjustment.Therefore,identifying changes in cultivated land and their ecological effects is of great significance for regional ecological protection.This study analyzed changes in land use from 1980 to 2020 and then estimated their ecological impact using the ecological impact index of cultivated land change based on normalized difference vegetation index (NDVI) and actual evapotranspiration data.In addition,changes in evapotranspiration were estimated to determine the degree of water consumption.The results show that:① the area of cultivated land in the basin has increased significantly from 7 273.22 km2 to 15 313.62 km2 over the past 40 years,an increase of 110.55%,mainly due to the reclamation of forests and wetlands;② in the past 20 years,there has been a significant conversion between paddy fields and dry land,with a greater increase in conversion from dry land to paddy fields;③ From 2000 to 2020,both NDVI and evapotranspiration in the basin showed an increasing trend,with an increased amplitude of 8.15% and 18.58%,respectively.The increase in NDVI in cultivated areas mainly occurs during the crop growing season,while the contribution of non-growing seasons to NDVI change is low;④ different types of changes in cultivated land have varying contributions to the NDVI and annual evapotranspiration in the basin.Returning cultivated land to forest has contributed to ecological protection and reduced water consumption.Although the reclamation of wetlands has increased NDVI during the growing season,it has also increased water consumption in the basin.The conversion from paddy fields to dry land is beneficial for water conservation in the basin,while the conversion from dry land to paddy fields increases evaporation and water consumption,potentially posing a risk to water resource security.